Universal character education to support inclusion for students with emotional and behavioural challenges - Garwood, Justin D (International Journal of Emerging Trends in Social Sciences, 2025)
One of the most popular approaches to supporting the emotional and behavioral needs of students with disabilities in inclusive general education classrooms is the implementation of Tier-one practices (e.g., behavior-specific praise, opportunities to respond) within a Positive Behavior Interventions and Supports (PBIS) framework. Although research has shown the promise of PBIS in supporting the needs of students with emotional and behavioral disorders (EBD), there is also recognition of the need for more intensive supports beyond PBIS practices to best address these students’ many challenges in finding success in school. One option is to combine a PBIS approach with social-emotional learning (SEL) to deliver a more intense level of support. The current article describes such a program – the Positivity Project (P2) and outlines the ways in which it may be able to support the needs of students with EBD.